IMPACT OF CERTAIN AGROCHEMICALS ON SHOOT AND FRUIT BORER (EARIAS VITTELLA FAB.) (LEPIDOPTERA: NOCTUIDAE) IN BHENDI (ABELMOSCHUS ESCULENTUS (L.) MOENCH) ECOSYSTEM - ARDHENDU CHAKRABORTY; K. KUMAR; A. S. MAILAPPA (The Bioscan, 2015)
Two supervised field experiments were conducted with the bhendi hybrid MH 10 during kharif, 2012 and rabi, 2012-13 to study the impact of agrochemicals on shoot and fruit borer damage. The agrochemicals used were fertilizer, insecticide and herbicide individually as well as in combinations. It was found that the shoot damage, fruit damage (number basis) and fruit damage (weight basis) was higher in the untreated check 20.63, 35.08 and 40.29 percent respectively while a low per cent damage was recorded in the treatment with insecticide alone8.01, 12.41 and 11.98 per cent respectively during kharif, 2012. In rabi, 2012-13, a higher per cent damage was recorded in the untreated check 20.38, 37.74 and 40.74 per centrespectively while a low per cent damage was observed in the treatment with insecticide 11.56, 18.89 and 20.03 per cent respectively. The per cent damage was higher in the treatment with fertilizer alone compared to the other treatments in both the seasons. The highest yield and benefit cost ratio was observed in the treatment with herbicide + fertilizer + insecticide, in both the seasons.Hence, a need based application of agrochemicals protect the ecosystem and exhibit a higher yield.